Copper (II) complexes with some antibiotics: synthesis, FT-IR study and in vitro antibacterial activity - Cipurković, Amira; Marić, Snježana; Horozić, Emir; Husejnagić, Darja; Cipurković, Suada (International Journal of Advanced Chemistry, 2023)
Copper (II) complexes with commercial antibiotics, amoxicillin (AMX), azithromycin (AZT) and ciprofloxacin (CFL) were synthesized and isolated as solids. Structures of the isolated products were determined by FTIR spectroscopy. Antibacterial activities were determined on reference bacterial strains from the ATCC collection by diffusion technique. The results show that AMX and CFL coordinate Cu (II) ion as bidentate O-donor ligand. AZT coordinates metal center as bidentate NO-donor ligand. A difference in the morphology of antibiotic crystals and the synthesized complexes was found. Complex of Cu (AMX)2 show complete absence of antibacterial activity, while the other com-plexes show the same or even lower activity than the parent ligands.